AKUNTABILITAS KERJA PADA PERUSAHAAN UMUM DAMRI STASIUN MANADO - Purukan, Johanes Jan William (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : Public Company DAMRI Station Manado as a government-owned company is expected to have performance accountability that can improve accountability of public services. However, the reality shows that today is faced with accountability issues both managerial and program. To analyse accountability of DAMRI Public Company of Manado Station either managerial or program in the effort of development of public administration management science, this research uses qualitative design. The conclusion of this study is that the cause of the lack of accountability at DAMRI Public Company Manado Station due to managerial accountability and program accountability as a ceremony over the responsibility of DAMRI Public Company Station Manado which is a public organization owned by the government that has not been able to manage the organization efficiently and effectively and has not shown program performance And has not provided an alternative program that can encourage DAMRI Public Company to achieve its vision and mission through the achievement of optimal results with minimal cost.Â Keywords: Accountability Work, Manajerial, Program.